Influence of scatter data and temperature lag on the analysis of thermoluminescence glow peak: A Monte Carlo simulation study. (January 2021) - Sadek, A.M.; Pagonis, Vasilis; Kitis, G.
Abstract: The effects of the scattering data that might appear at the low radiation doses and the temperature lag that might occur between the heater pan and the detector on the thermoluminescence (TL) glow-curve have been addressed. The scattering data were mathematically induced in the TL glow curve using the Monte Carlo (MC) algorithm. While the phenomenon of the temperature lag has been simulated, assuming an exponential function. The deconvolution analysis has been carried out by TL expressions based on a presumed kinetics order value in comparison with the general-order kinetics equation. It has been found that even though the glow peak is known to obey the first- or second-order kinetics model, using the general-order kinetics equation in the deconvolution analysis is better than using the corresponding model equation. Highlights: The effects of scattering data and temperature lag on TL peak have been investigated. The scattering data and temperature lag influence the shape of the TL peak. Fitting the peak with a presumed order of kinetics values may yield poor-fitting quality. The GOK equation is recommended in the analysis even for first/second-order peaks.